Cytomorphological features of cystic neutrophilic granulomatous mastitis on ThinPrep. Issue 11 (24th October 2018) - Patel, Ami; Sung, Simon; Hoda, Syed A.; Westblade, Lars F.; D'Alfonso, Timothy; Rao, Rema
Abstract: Granulomatous mastitis (GM) is an uncommon entity and challenging to distinguish from breast carcinoma, both clinically and upon imaging. Cystic neutrophilic granulomatous mastitis (CNGM) is a histologically distinct GM with clear "cystic" spaces (CS) surrounded by neutrophils and may contain Gram‐positive bacilli (such as Corynebacterium species). Cytologic features of GM, in particular CNGM, on ThinPrep (TP), are limited. We reviewed the cytological features of GM with a special focus on CNGM on TP. Ten cases with a concurrent/recent FNA and histologic diagnosis of GM or CNGM, or positive culture for Corynebacterium kroppenstedtii, were identified over an 11‐y period (2007‐2017). A double‐blinded review of the TP slides was performed by two independent cytopathologists. Data were analysed using Fisher's exact test. Six cases were histologically proven CNGM and 1 FNA only case had a positive culture for C. kroppenstedtii . Three had a histological diagnosis of GM. TP from the 7 CNGM cases demonstrated CS, including 1 case with a cellblock (CB) study showing well‐formed clear CS, while none of the non‐CNGM cases had CS ( P = .01 ) . Bacteria were identified within CS in 5 of 7 cases of CNGM. Multinucleated giant cells, granulomas, histiocytes, and neutrophils were variably observed. All histologically confirmed cases of CNGM showed distinct CS on TP. Cellblock study is a valuable adjunct to evaluate CNGM and for ancillary studies. Although our study was limited by a small sample size, our findings necessitate the need for studies with a larger cohort.